Anemia in centenarians: prevalence and association with kidney function. Issue 1 (1st January 2020) - Jia, Wangping; Wang, Shengshu; Liu, Miao; Yang, Shanshan; Cao, Wenzhe; Han, Ke; He, Yao
ABSTRACT: Objectives: Although anemia is a widespread condition that leads to an increase in morbidity and mortality, particularly as people age, little information on anemia in centenarians is available. The objective of this study was to determine the prevalence of anemia and examine the relationship between anemia and a decline in kidney function in Chinese centenarians. Methods: We conducted a population-based cross-sectional study of a sample of 1002 Chinese centenarians (180 men and 822 women) from 2014 to 2016. Anemia was defined as a hemoglobin level of <130 g/L for men and <120 g/L for women. Results: The prevalence of anemia and severe anemia (<100 g/L) were 68.5% (men, 76.1%; women, 66.8%) and 19.6% (men, 16.1%; women, 20.3%), respectively. The risk of anemia and estimated glomerular filtration rate (eGFR) showed a nonlinear relationship (nonlinear P = 0.021). The interaction analysis revealed that ethnicity and diabetes mellitus played a role in the association between the eGFR (<60 mL/min/1.73 m 2 ) and anemia. Conclusion: Anemia is highly prevalent in Chinese centenarians, particularly among men. Decreased kidney function was an independent determinant of anemia, especially in Han participants and participants with diabetes mellitus. The possibility of decreased kidney function needs to be considered in the evaluation and treatment of anemia in centenarians.